Penjara sebagai Ruang Ideologis dalam Film Ghost in the Cell: Perspektif Spatial Ideology Henri Lefebvre - Febrian Putra; Bhimo Wicaksono Makardi; Aninditya Ardhana Riswari (Institut Seni Indoensia Surakarta, 2026)
This article examines the prison as an ideological space in the film Ghost in the Cell directed by Joko Anwar through Henri Lefebvre’s spatial ideology perspective. The study is grounded in the development of spatial criticism in cinema, which views space not merely as a narrative setting but as a socio-political construction representing power relations and ideology. This research employs a qualitative approach within an interpretive-critical paradigm. The research data consist of the film’s visual and narrative elements, including mise-en-scène, cinematography, lighting, spatial setting, dialogue, and narrative structure. The data are analyzed using cinematic close reading by applying Lefebvre’s spatial triad: spatial practice, representations of space, and representational spaces. The findings reveal that the prison space in the film is produced as an ideological mechanism representing bodily discipline, state surveillance, structural corruption, and social resistance. Spatial practice is reflected in disciplinary routines and the control of prisoners’ bodies. Representations of space are manifested through prison architecture, surveillance systems, and visual hierarchies that symbolize state power. Meanwhile, representational spaces emerge through prisoners’ emotional experiences, collective solidarity, and supernatural elements as symbolic resistance against the repressive system. This study concludes that the film employs prison space as an allegory of the state and as a medium of socio-political criticism in contemporary Indonesian cinema.